DEPRESSIVE SYMPTOMS FOLLOWING SPOUSAL LOSS FOR MEN AND WOMEN: THE BUFFERING EFFECTS OF PSYCHOLOGICAL RESILIENCE. (11th November 2018) - King, B; Carr, D; Taylor, M
Abstract: Spousal loss is often associated with increased emotional distress, especially depressive symptoms, with previous research showing that men are particularly vulnerable to the negative consequences of widowhood. Little research, however, has explored what factors lead some to experience more significant increases in depressive symptoms than others. Recent research suggests that psychological resilience may play a role in this process. The current study uses data from the Health and Retirement Study (HRS) to examine a change in self-reported depressive symptoms of men and women who experience spousal loss compared to those who remain continuously married (N=5, 626). A simplified resilience index was developed using data drawn from the psychosocial and lifestyle questionnaire, and a pooled dataset of continuously married men and women, some who became widowed, was developed based on completion of this measure at baseline. Ordinary Least Squares (OLS) Regression was used to assess depression following reported spousal loss for widows relative to their continuously married counterparts. Results show that pre-bereavement resilience mediated change in depressive symptoms (CES-D) following spousal loss, and these effects varied by gender. Overall, women experienced less significant increases in depressive symptoms following widowhood than men, and widows and married individuals with low resilience had similar increases. Widowed women with high resilience experienced little improvement relative to their low resilience counterparts. However, widowed men with low resilience experienced significant increases in depression (approximately three additional symptoms), and men with high resilience experienced no increases in depressive symptoms regardless of widowhood status.